Thrombocytosis in Febrile Illness in Children of Age Three Months to 14 Years at a Tertiary Care Hospital of Nepal - Thakur, Sajan Kumar; Kattel, Pramod (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Acute febrile illness is common presentation in children. Thrombocytosis can be used as a predictor of febrile illness in children. The objectives of this study were to find out the prevalence and causes of thrombocytosis among febrile children and to access the utility of platelet count as a potential predictor of serious bacterial infection alone or in association with other predictors.Material and Methods: A cross-sectional descriptive study was done in 290 febrile children following convenience sampling method. Statistical analysis was done using SPSS. Univariate analysis using chi-square test for categorical and independent samples and “t” test for continuous variables were done.Results: Thrombocytosis was present in 13.1% of cases. Most cases had mild thrombocytosis (10%) whereas moderate thrombocytosis was present in 2.8% of cases and 0.3% cases had severe thrombocytosis. Lymphocyte level, erythrocyte sedimentation rate and C-reactive protein also showed a significant association with thrombocytosis (p